2007
DOI: 10.1007/s00381-007-0330-9
|View full text |Cite
|
Sign up to set email alerts
|

Spatial perception predicts laparoscopic skills on virtual reality laparoscopy simulator

Abstract: Among novices, visual-spatial perception is associated with manual skills performed on a virtual reality simulator. This result may be important for educators to develop adequate training programs that can be individually adapted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
2
2

Year Published

2008
2008
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(31 citation statements)
references
References 16 publications
0
27
2
2
Order By: Relevance
“…In contrast to advanced laparoscopic surgeons, the self-belief of novices seemed to be independent of performance, indicating that training was more important than high levels of self-belief [58]. Innate visual-spatial perception, however, seemed to correlate positively with better performance of novices, indicating the possibility of this trait being used as a selection tool for candidates entering surgical training [59].…”
Section: Nontechnical Aspects Of Surgical Performancementioning
confidence: 92%
See 1 more Smart Citation
“…In contrast to advanced laparoscopic surgeons, the self-belief of novices seemed to be independent of performance, indicating that training was more important than high levels of self-belief [58]. Innate visual-spatial perception, however, seemed to correlate positively with better performance of novices, indicating the possibility of this trait being used as a selection tool for candidates entering surgical training [59].…”
Section: Nontechnical Aspects Of Surgical Performancementioning
confidence: 92%
“…Other studies performed with the LapSim have investigated the impact of self-belief [58] and innate visual-spatial perception [59] on surgical performance. Interestingly, high levels of self-belief in novices correlated negatively with laparoscopic skills.…”
Section: Nontechnical Aspects Of Surgical Performancementioning
confidence: 99%
“…In a study by Hassan et al the correlation between visual-spatial perception and laparoscopic skills on virtual reality laparoscopy simulator was investigated (16). The participants underwent laparoscopic training that comprised coordination, cutting and clip application.…”
Section: Discussionmentioning
confidence: 99%
“…As is noticed in our material, skills at baseline vary between individuals and we could see that some individuals with bad stereoacuity had difficulties in improving their performance score. Others have shown that previous computer experience and visuo-spatial skills affect performance on VR surgery simulators (Hassan et al 2007;Rosser et al 2007). Schijven & Jakimowicz (2004) found in their study one group that did not benefit from training despite their low initial scores and in ophthalmology, it has been reported that around 10% of residents have difficulties in learning surgical skills (Binenbaum & Volpe 2006).…”
Section: Discussionmentioning
confidence: 99%